Pelaksanaan Supervisi Pendidikan dalam Meningkatkan Kualitas Pembelajaran - Dimas Zuhri Ahmad; Agus Gunawan; Atang Suryana; Eneng Siti Suherni; Sri Mulyani (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
Success in the realm of education can not only be measured based on the end result, but it is more essential to understand and study the effectiveness of the implementation of school management functions, including planning, implementation, evaluation and RTL (follow-up plan). Supervision of education, as a process of supervision and guidance, aims to improve the quality of education in educational institutions. The focus of this article is the implementation of educational supervision carried out by the principal and supervisory team at SMP Nurul Ilmi Darunnajah. This study used qualitative descriptive method with data collection techniques through interviews, observation, and documentation. The results of this study cover several aspects, including: 1) The principal conducts supervision which includes two things, namely teacher administration and teaching and learning process activities, 2) Supervision brings significant benefits to teachers in handling various educational problems during learning, while providing motivation to teachers to continue to improve their knowledge, making them professional teachers in carrying out learning, 3) The headmaster faces obstacles in supervision, especially related to overlapping activities